Biodegradable composite material for orthopedic applications: some considerations on microstructural characterization, electrochemistry and mechanical properties. (Innovation & Development in Engineering and Applied Science, 2023)
In recent years, a new wave of biomaterials have been developed for a variety of applications. Researchers have focused on improving the essential characteristics and properties of biomaterials in orthopedic applications. Biocompatibility, bioactivity, and control of corrosion mechanisms in biodegradable materials have been the target of study and development of new innovative materials in this area of science. biomedical. By implementing the addition of a reinforcing ceramic material in a biodegradable metal alloy matrix, several of these characteristics can be improved, and in addition to these, mechanical, surface and even osseointegration properties. In this review, an attempt will be made to provide a context for the microstructural, electrochemical, and mechanical characterization of these biomaterials. as well as applications and synthesis techniques.
Keywords: Biodegradable materials; composite materials; corrosion; characterization techniques; biocompatibility